Cross-linked composite proton conductive membranes - Zhyhailo, M.M.; Yevchuk, I.Yu.; Demchyna, O.I.; Kochubei, V.V.; Makota, O.I. (Physics and Chemistry of Solid State, 2021)
Using UV-curing technique the proton conductive polymer materials based on acrylic monomers: 2-acrylamido-2-methylpropane sulfonic acid (AMPS), acrylic acid (AA) and acrylonitrile (AN), cross-linked by varying amounts of N,N'-methylene(bis)acrylamide (MBA), and the hybrid polymer/inorganic membrane of the same content with addition of sol-gel system (SGS) based on 3-methacryloxypropyl trimethoxysilane (MAPTMS) and tetraethoxysilane (TEOS) were synthesized. The obtained materials were characterized by analysis of thermal, mechanical and morphological properties. Proton conductivity and water uptake were found to depend on the level of cross-linking of the materials. The value of proton conductivity of the hybrid membrane was sufficiently high reaching 3.46 × 10-2 S cm-1.